ECOLOGY AND DIVERSITY OF PLANKTONS IN LAKES OF UCHALLI WETLANDS COMPLEX, PAKISTAN - Z. Ali; S.S. Ahmad; M. Akhtar; M. A. Khan; M.N. Khan (Journal of Animal and Plant Sciences, 2007)
Limnological studies have been made by several workers in Pakistan and abroad, keeping in view their strong impact on wetland’s biodiversity. At Uchalli Wetlands Complex no significant contribution were made prior to this communication. Uchalli Wetlands Complex is a Ramsar site in Pakistan where globally endangered species visit every year. In the present study the results on physico-chemical characteristics of water along with plankton ecology of three lakes are highlighted. The results revealed that among total 103 species of planktons, 51 were found in Uchalli, 47 in Khabbaki and 39 in Jahalar lake, and 31 % species were phytoplanktons, while 69 % were zooplanktons.
Keywords: Bio-chemical water analysis; Planktonic analysis; Uchalli Wetlands Complex; Pakistan